2021
DOI: 10.3390/math10010007
|View full text |Cite
|
Sign up to set email alerts
|

Rotating Flow in a Nanofluid with CNT Nanoparticles over a Stretching/Shrinking Surface

Abstract: The steady three-dimensional rotating flow past a stretching/shrinking surface in water and kerosene-based nanofluids containing single and multi-walled carbon nanotubes (CNTs) is investigated. The governing equations are converted to similarity equations, and then numerically solved using MATLAB software. The impacts of rotational, suction, and nanoparticle volume fraction on the flow and the thermal fields, as well as velocity and temperature gradients at the surface, are represented graphically and are anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The paper by N.A. Yacob et al [9] studies rotating flow in nanofluids over a permeable stretching/shrinking surface. The authors present the numerical results obtained with MATLAB software, starting from a mathematical model with carbon nanotubes (single and multi-walled), and analyse the heat and mass transfer characteristics, and also the stability of the considered solutions.…”
Section: Description Of Published Papersmentioning
confidence: 99%
“…The paper by N.A. Yacob et al [9] studies rotating flow in nanofluids over a permeable stretching/shrinking surface. The authors present the numerical results obtained with MATLAB software, starting from a mathematical model with carbon nanotubes (single and multi-walled), and analyse the heat and mass transfer characteristics, and also the stability of the considered solutions.…”
Section: Description Of Published Papersmentioning
confidence: 99%
“…Takhar et al 16 further studied the effects of MHD flow. Yacob et al 17 reported on the steady rotating flow of fluids over an extendable or shrinkable surface. Rana et al18 performed finite element simulations to study the unsteady MHD flow with rotational effects.…”
Section: Introductionmentioning
confidence: 99%
“…The results also show that thermal radiation and the unsteadiness parameter stimulate the temperature. Nor A. Yacoub [29] numerically investigated 3D rotating flow in water and kerosene-based nanofluids with single and multi-walled CNT nanoparticles over a shrinking/stretching surface. The results show that heat transfer is enhanced when the nanoparticle volume fraction or suction parameter increases, whereas it is reduced with increments in the rotating flow parameter.…”
Section: Introductionmentioning
confidence: 99%